2021
DOI: 10.3390/photonics8040107
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Deflectors Made of Dielectric Nanohole Arrays with Anti-Damage Potential

Abstract: In intense-light systems, the traditional discrete optical components lead to high complexity and high cost. Metasurfaces, which have received increasing attention due to the ability to locally manipulate the amplitude, phase, and polarization of light, are promising for addressing this issue. In the study, a metasurface-based reflective deflector is investigated which is composed of silicon nanohole arrays that confine the strongest electric field in the air zone. Subsequently, the in-air electric field does … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
3
1
Order By: Relevance
“…The melting point of silicon is 1683 K. It is shown that the meta-film can handle the maximum laser power (0.0992 W per 0.36 µm 2 ), i.e., the laser density of 0.27 W/µm 2 . This power value is higher than that (0.24 W/µm 2 ) in our previous work of meta-deflectors [33].…”
Section: Resultscontrasting
confidence: 67%
See 2 more Smart Citations
“…The melting point of silicon is 1683 K. It is shown that the meta-film can handle the maximum laser power (0.0992 W per 0.36 µm 2 ), i.e., the laser density of 0.27 W/µm 2 . This power value is higher than that (0.24 W/µm 2 ) in our previous work of meta-deflectors [33].…”
Section: Resultscontrasting
confidence: 67%
“…Each unit-cell possesses an ellipse nanohole with diameters Dx and Dy. Compared to the rectangular shape in our previous work [33], the ellipse has a smoother edge and lower surface energy, leading to weaker localized fields and better thermal stability. Compared to symmetrical structures such as nanocylinders, ellipses have one more parameter (i.e., D vs. Dx, Dy) to tune the field distribution inside.…”
Section: Methodsmentioning
confidence: 77%
See 1 more Smart Citation
“…This method has been experimentally verified in anti-reflection nanotextures on fused silica, in which the strong electric field is tuned from nanostructures into the air and anti-damage properties are obtained successfully [27,28]. According to the method, our previous works also demonstrated that reflective metasurfaces made of dielectric nanoholes could be realized with high damage thresholds via field manipulation, and the electromagnetic mechanism has been explained via the electromagnetic distribution of excitation states [29,30]. To further demonstrate the principles of anti-damage metasurfaces, the optothermal mechanism in transmissive phase-control metalenses still requires investigation.…”
Section: Introductionmentioning
confidence: 85%